Identification of Place Identity Characteristics in Walking Tour of Peneleh Heritage Kampong, Surabaya City, Indonesia - Prathama, Dimas Wahyu Aji; Idajati, Hertiari (Media Konservasi, 2024)
Peneleh Kampong in Surabaya, Indonesia, is a significant heritage area known for its walking tour activities organized by the local community group, Begandring Soerabaia, since 2021. This study aims to identify and analyze the characteristics of these walking tours using the place identity approach, addressing management issues that may affect the area's identity. Data were collected through in-depth interviews with key community members and analyzed using content analysis. The findings reveal 107 characteristic points of walking tour management, distributed across three aspects: physical settings (34 citations, 31.78%), activities (39 citations, 36.45%), and meanings (34 citations, 31.78%). These insights contribute to the preservation of the cultural heritage in Peneleh Kampong and support sustainable tourism development by strengthening its place identity. This research underscores the importance of community involvement and strategic management in enhancing heritage tourism experiences.